2007
DOI: 10.1063/1.2800293
|View full text |Cite
|
Sign up to set email alerts
|

Coherence in Y-coupled quantum cascade lasers

Abstract: A monolithic coupling scheme in which two active waveguides merge into a single waveguide is presented for a GaAs∕AlGaAs quantum cascade laser. The evolving fields interfere and a constant phase is observed in the Y-shaped laser cavity, resulting in a far field pattern of a double slit. The mode distribution is comprehensively derived by matching the far field profiles to simulated values and shows a weak current dependence. The device demonstrates the feasibility of coherent laser resonators with prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…21 Two spatially separated modes are coupled laterally into the same ridge. Due to the large bending radius of the merging branches, the mode propagation can be treated as one-dimensional.…”
Section: Cavity Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Two spatially separated modes are coupled laterally into the same ridge. Due to the large bending radius of the merging branches, the mode propagation can be treated as one-dimensional.…”
Section: Cavity Modesmentioning
confidence: 99%
“…θ ≈ 1), two field configurations exist within the Y-shaped cavity. 21 A two-dimensional schematic view is given in Figure 3. The corresponding cavity modes have even or odd symmetry.…”
Section: Cavity Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the impacts of coupling length and wavelength variations on the coupling had revealed that the phase-locked emission strongly depends on the length of the coupling region and also on the ratio between waveguide width and emission wavelength [31,32]. This understanding of the coupling mechanism is important to exploit Y-coupling in midinfrared QCL arrays with complex structures for high output performance.…”
Section: Brief Review Of Qcl Arraysmentioning
confidence: 99%
“…Obtaining the coherence within an array relies on the ability to control the coupling between individual lasers. Inspired by concepts developed in more mature, shorter wavelength diode laser systems, several coupling schemes, including coupling through exponentially decaying fields outside the high index dielectric core (evanescent-wave coupled) [27][28][29], through feedback from external reflectors (diffraction-wave coupled) [30], connecting two ridges to one single-mode waveguide (Y coupled or tree coupled) [31][32][33][34][35], through lateral propagating waves (leaky-wave coupled) [36][37][38] and combining gradedphotonic-heterostructure (GPH) QCLs with a ring resonator [39], have exhibited excellent performance on phase-locking QCL arrays, especially in mid-infrared range.…”
Section: Brief Review Of Qcl Arraysmentioning
confidence: 99%